Functional analysis of Paracoccidioides brasiliensis 14-3-3 adhesin expressed in Saccharomyces cerevisiae Microbe-host interactions and microbial pathogenicity - Assato, Patricia Akemi [UNESP]; Da Silva, Julhiany De Fátima [UNESP]; De Oliveira, Haroldo Cesar [UNESP]; Marcos, Caroline Maria [UNESP]; Rossi, Danuza [UNESP]; Valentini, Sandro Roberto [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Fusco-Almeida, Ana Marisa [UNESP] (Springer Nature, 2015)
Background: 14-3-3 proteins comprise a family of eukaryotic multifunctional proteins involved in several cellular processes. The Pb14-3-3 of Paracoccidioides brasiliensis seems to play an important role in the Paracoccidioides-host interaction. Paracoccidioides brasiliensis is an etiological agent of paracoccidioidomycosis, which is a systemic mycosis that is endemic in Latin America. In the initial steps of the infection, Paracoccidioides spp. synthetizes adhesins that allow it to adhere and invade host cells. Therefore, the aim of this work was to perform a functional analysis of Pb14-3-3 using Saccharomyces cerevisiae as a model. Results: The functional analysis of Pb14-3-3 was performed in S. cerevisiae, and it was found that Pb14-3-3 partially complemented S. cerevisiae proteins Bmh1p and Bmh2p, which are recognized as two yeast 14-3-3 homologues. When we evaluated the adhesion profile of S. cerevisiae transformants, Pb14-3-3 acted as an adhesin in S. cerevisiae; however, Bmh1p did not show this function. The influence of Pb14-3-3 in S. cerevisiae ergosterol pathway was also evaluated and our results showed that Pb14-3-3 up-regulates genes involved in ergosterol biosynthesis. Conclusions: Our data showed that Pb14-3-3 was able to partially complement Bmh1p and Bmh2p proteins in S. cerevisiae; however, we suggest that Pb14-3-3 has a differential role as an adhesin. In addition, Pb-14-3-3 may be involved in Paracoccidioides spp. ergosterol biosynthesis which makes it an interest as a therapeutic target.
Keywords: 14-3-3 protein; Adhesin; Adhesion; Paracoccidioides brasiliensis